Gamma irradiation-induced evolution of the transformation temperatures and thermodynamic parameters in a CuZnAl shape memory alloy - Tatar, C (Elsevier, 2005)
The effect of the gamma irradiation on transformation temperatures and thermodynamic parameters of the CuZnAl shape memory alloy irradiated with different doses has been investigated. The evolution of transformation temperatures was studied by differential scanning calorimetry (DSC). It was found that the gamma irradiation have a prominent effect on the transformation parameters of the CuZnAl shape memory alloy. The temperature M-f, A(s) and A(f) shift by the different amount as M-s. It is found that the elastic strain energy and Gibbs free energy decreased by about 27 and 47% with gamma irradiation applied, respectively. The nominal displacement per atom (dpa) level was estimated as similar to 10(-5). (C) 2005 Elsevier B.V. All rights reserved.
Keywords: shape memory; Gibbs free energy; elastic strain energy